Fundamental aspects of operational risk and insurance analytics : a handbook of operational risk - Cruz, Marcelo G.; Peters, Gareth W., 1978-; Shevchenko, Pavel V. (Hoboken, New Jersey : Wiley, 2015)
"Co-edited by acknowledged experts in the quantification of operational risk, Handbook of Operational Risk conveniently and systematically displays all of the financial engineering topics, theories, applications, and current statistical methodologies that are intrinsic to the subject matter. This one-stop guide for financial engineers, quantitative analysts, and risk managers places under one cover all of the necessary theory, applications, and models that are inherent in any discussion of the subject. The authors emphasize the importance of collecting high-quality data based upon understanding the problems that impede the gathering process"--
"Systematically displays all of the financial engineering topics, theories, applications, and current statistical methodologies that are intrinsic to the quantification of operational risk"--
Includes bibliographical references and index.
Keywords: Operational risk; Risk management; MATHEMATICS / Probability & Statistics / General